Cross and Resurrection : God's Wonder and Mystery - Schwarzwäller, Klaus (Book collections on Project MUSE., 2012)
"German theologian, Klaus Schwarzwl̇ler reclaims Christ's cross and resurrection as God's wonder and mystery. He connects with art, history, contemporary culture, and especially scripture in presenting a trenchant analysis of the modes of power and production that have undergirded both society and the church since the Enlightenment. The church in the present era comes under the power of the Enlightenment's quest for truth in the measurable, reproducible, and rational. The proof of the Spirit's power thus comes to depend on the criteria of reason and theory, rather than on the Spirit's work in the reality of daily life. When the church and theology operate in this way, the cross and resurrection become something that requires our management, manipulation, or expert interpretation. Thus, the church and theology wind up existing for their own ends, and freedom and faith are replaced with brutal indifference and control. The truth of the gospel is that on the cross Christ bore the brunt of power and production that could not bear his utter devotion to God and care for the powerless. The cross excludes our control and the power of the resurrection ensures that the negativity of human life borne on the cross will be overcome. Schwarzwl̇ler calls the church and theologians to relinquish both their conformity to society and the indifference that power and production create and instead focus on tending to God's word so that the cross and resurrection are again revealed as God's wonder and mystery"--Publisher description.